ENHANCEMENT OF SOLUBILITY OF RILPIVIRINE BY INCLUSION COMPLEXATION WITH CYCLODEXTRINS (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Rilpivirine having lowest water solubility indicates class II drugs of BCS. These classes of drugs could potentially exhibit dissolution rate limited absorption. The objective of the present study is to improve the solubility and dissolution of Rilpivirine through inclusion complexation with βCD and HPβCD. Solid binary systems of Rilpivirine with βCD and HPβCD were prepared by solvent evaporation and kneading methods at 1:1 and 1:2 M ratios. The prepared solid binary systems were studied in solution state by phase solubility, in vitro dissolution rate and solid state by FTIR and XRD. The dissolution parameters were studied by using dissolution software PCP Disso V3. The drug content was uniform in all the solid binary systems with low SD and CV values. The apparent stability constant indicates there is a 1:1 stochiometric complex with βCD and HPβCD. The formation of inclusion complexes with βCD and HPβCD in the solid state were confirmed by FTIR, XRD. The dissolution data clearly suggest drug release was method dependent and type of cyclodextrin. The dissolution of solid binary systems obeyed first-order kinetics and model fitted with Hixon crowel. A true inclusion complex of Rilpivirine was observed with βCD and HPβCD. Dissolution properties of solid binary systems were superior then rilpivirine alone and its corresponding physical mixtures. Overall dissolution rate was solvent evaporation > kneaded binary systems > physical mixture > pure drug. One-way ANOVA results suggest the DE30 and DE60 values were significantly higher (P<0.05) in solid binary systems when compared to physical mixture and pure drug.